[OP.7C.08] BLOOD-PRESSURE ASSOCIATED VARIANTS IN NPR3 AFFECT HUMAN VASCULAR SMOOTH MUSCLE CELLS PROLIFERATION AND CALCIUM RESPONSE TO ANGIOTENSIN II. (September 2016) - Ren, M.; Ng, F.; Witkowska, K.; Baron, M.; Townsend-Nicholson, A.; Xiao, Q.; Hobbs, A.; Ye, S.; Caulfield, M.J.
Abstract : Objective: A recent genome-wide association study identified a locus within natriuretic peptide receptor C (NPR3) to be significantly associated with blood pressure (BP), To functionally characterise the effect of BP- associated SNPs (single nucleotide polymorphisms) at the NPR3 locus in the context of BP regulatory pathways Figure. No caption available. Design and method: Primary human umbilical artery smooth muscle (HUASMCs) and vein endothelial (HUVECs) cells were genotyped for BP-associated NPR3 variants. Endogenous mRNA and protein expression levels were assessed by qRT-PCR, allelic expression imbalance assay and western blotting. Open chromatin regions were assayed using formaldehyde-assisted isolation of regulatory elements (FAIRE). Interaction between variants flanking region with nuclear protein was detected by electrophoretic mobility shift assay (EMSA). Cell proliferation and migration were determined by cell counting and scratch assays. Angiotensin II (Ang II)-induced calcium flux was evaluated using the intracellular fluorescent probe. Results: The BP-elevating allele of the NPR3 variants in rs1173771 linkage disequilibrium (LD) block was associated with lower endogenous mRNA and protein levels in HUASMCs. This is consistent with the finding that BP-elevating allele is less located within open chromatin. The decreased NPR3 expression in HUASMCs carrying the BP-elevating allele is associated with increased cell proliferation and intracellular calcium flux in response to Ang II stimulation. No differences in migration rates were detected. No genotype-dependent characteristics were observed in HUVECs NPR3 expression and cell proliferation. Conclusions: This study has identified a potential mechanism for BP-associated SNPs at NPR3 locus to influence BP predominantly via an effect on vascular smooth muscle cell behaviors.